Situating Daisaku Ikeda’s essential elements of global citizenship within contemporary scholarship: a qualitative meta-synthesis - Sherman, Paul; Boukydis, Olivia (International journal of development education and global learning (Print), 2023)
This article reports on meta-synthesis research that examined contemporary scholarship on global citizenship for the purpose of identifying a possible alignment with Daisaku Ikeda’s views on global citizenship. Thirty relatively contemporary scholarly articles on the subject matter were examined using a qualitative meta-synthesis methodology. Ikeda’s speech entitled ‘Thoughts on education for global citizenship’, delivered over 25 years ago at Columbia University’s Teachers College, USA, contains his most frequently cited ideas on the salient conditions required for global citizenship. As Ikeda is a thoughtful and prolific author on the subject of global citizenship, there is merit in exploring the alignment of his ideas about this concept with those articulated in contemporary scholarship. Conducting a meta-synthesis through the lens of Ikeda’s essential elements of global citizenship has helped to identify potentially useful contributions to the global citizenship discourse. This article highlights salient common themes of global citizenship uncovered through the meta-synthesis research, as well as providing an alternative definition of global citizenship gleaned from the findings.